PERANCANGAN KAPAL BULK CARRIER 11500 DWT KECEPATAN 12 KNOT DENGAN RUTE PELAYARAN LHOKSEUAMAWE (ACEH) - TANJUNG EMAS (SEMARANG) - Muhammad Nashiir, (2021)
Bulk cargo ships or better known as bulk ships are ships that carry a variety of bulk cargo. Free loads carried are coffee beans and corn seeds that are ready to be transported. Bulk Carrier ships are equipped with one deck that can make ships carry large amounts of cargo. The main size of the ship was obtained through the method of two comparative data obtained from Bureau Veritas (Register France). In this proposal the authors designed a bulk ship with a speed of 12 knots with the Aceh-Semarang route with the main size of the ship LOA:, LPP:, B:, H: , T:, CB: And hydrostatic keriteria, heavy ships, strength, construction, maneuvering, defense, propulsion, difficulties, security, safety, and seaworthiness of ships and shipping vessels that have been fulfilled.